Answer:
![f(x)=x^3+x^2-4x-4](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E3%2Bx%5E2-4x-4)
Step-by-step explanation:
Graph of a cubic polynomial that falls to the left and rises to the right with x intercepts negative 2, negative 1, and 2
x intercepts are -2, -1, 2
We write the x intercepts in factor form
f(x)= (x-p)(x-q)(x-r)
where p, q and r are the x intercepts
f(x)= (x-(-2))(x-(-1))(x-2)
f(x)= (x+2)(x+1)(x-2)
now we multiply the parenthesis using FOIL method
(x+2)(x+1)= x^2 +2x+x+2= x^2+3x+2
![f(x)= (x^2+3x+2)(x-2)](https://tex.z-dn.net/?f=f%28x%29%3D%20%28x%5E2%2B3x%2B2%29%28x-2%29)
now we multiply with (x-2)
x^3-2x^2 +3x^2-6x+2x-4
combine like terms
![f(x)=x^3+x^2-4x-4](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E3%2Bx%5E2-4x-4)